Adverse Drug Reaction and Preliminary Efficacy of Dioscorea bulbifera Linn. gel on Wound Healing in Thai Patients - Tungsukruthai, Parunkul; Sriyakul, Kusuma; Soisamrong, Mala; Loapiyasakul, Kanyarat; Jumpa-Ngern, Piracha (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 4 (2022): October-December 2022, 2022)
The lack of access to specialized wound care has resulted in amputations and loss of work productivity and medical cost estimates for chronic wound treatments are high worldwide. The objective of this study was to examine the safety and efficacy of Dioscorea bulbifera Linn. on wound healing in Thai patients before seeking the addition of this drug to the Thai National List of Essential Drugs. This study was conducted in 18 government hospitals from November 2019 to February 2020 with 1,026 OPD and IPD patients. Trained interviewers introduced themselves, explained the purpose of this study to participants, and followed up after using Dioscorea bulbifera Linn gel for 4 weeks at which time measurements were taken using the adverse drug reaction assessment using the Naranjo algorithm, wound characteristics and size. In addition, interviews were used to ascertain patient satisfaction with the drug. The results showed adverse drug reactions in only one patient. Importantly, wound sizes were significantly reduced. Furthermore, 99% of patients would use this drug in the future. These findings provide more evidence to support the traditional use of Dioscorea bulbifera Linn for the treatment of wounds, and this evidence could support its entry into the national list of herbal medicines in Thailand. Keywords: Dioscorea bulbifera Linn, chronic wound, Wan Phra Chim herb, adverse drug reaction